(untitled) (Oxford, N.Y., 2002)
Enzyme assays are among the most frequently performed procedures in biochemistry and are routinely used to estimate the amount of enzyme present in a cell or tissue, to follow the purification of an enzyme, or to determine the kinetic parameters of a system. The range of techniques used to measure the rate of an enzyme-catalysed reaction is limited only by the nature of the chemical change and the ingenuity of the investigator. This book describes the design and execution of enzyme assays, covering both general principles and specific chapters.
Keywords: Enzymes; Analysis